2013
DOI: 10.1177/0022034513497751
|View full text |Cite
|
Sign up to set email alerts
|

Increased Enamel Hypoplasia and Very Low Birthweight Infants

Abstract: Birth cohort studies of developmental defects of enamel (DDE) and early childhood caries (ECC) in very low birthweight (VLBW) and normal birthweight (NBW) infants are rare. In this birth cohort of 234 VLBW and 234 NBW infants, we report the incidence of ECC and DDE at 8 and 18-20 mos of corrected age. Infant medical and maternal socio-demographic data were abstracted from medical records at birth. Dental assessments for ECC and DDE (enamel hypoplasia, demarcated and diffuse opacities) were completed at 8 and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(72 citation statements)
references
References 19 publications
5
65
0
2
Order By: Relevance
“…In the literature, LBW was not associated with dental caries in the primary dentition [Shulman, 2005;Tanaka and Miyake, 2014;Nirunsittirat et al, 2016]. The association between LBW and DDE found in other studies [Lunardelli and Peres, 2006;Ferrini et al, 2008;Velló et al, 2010;Takaoka et al, 2011;Cruvinel et al, 2012;Masumo et al, 2013;Nelson et al, 2013;Elfrink et al, 2014] was confirmed by the present data. Although in the literature mainly hypoplasia was associated with LBW [Aine et al, 2000;Velló et al, 2010;Masumo et al, 2013], in our study all types of DDE were associated with LBW.…”
Section: Risk Factorssupporting
confidence: 89%
See 2 more Smart Citations
“…In the literature, LBW was not associated with dental caries in the primary dentition [Shulman, 2005;Tanaka and Miyake, 2014;Nirunsittirat et al, 2016]. The association between LBW and DDE found in other studies [Lunardelli and Peres, 2006;Ferrini et al, 2008;Velló et al, 2010;Takaoka et al, 2011;Cruvinel et al, 2012;Masumo et al, 2013;Nelson et al, 2013;Elfrink et al, 2014] was confirmed by the present data. Although in the literature mainly hypoplasia was associated with LBW [Aine et al, 2000;Velló et al, 2010;Masumo et al, 2013], in our study all types of DDE were associated with LBW.…”
Section: Risk Factorssupporting
confidence: 89%
“…This might have contributed to reaching also families with a low or moderate health care compliance. Furthermore, the highest prevalence of DDE (90.0%) occurred in PTI with ELBW, which confirms previous observations that ELBW is associated with a high prevalence of DDE in the primary dentition [Ferrini et al, 2008;Cruvinel et al, 2012;Correa-Faria et al, 2013;Masumo et al, 2013;Nelson et al, 2013;Elfrink et al, 2014]. In the PTI-G significantly more tooth surfaces were affected by all types of DDE and the highest occurrence was recorded in PTI with ELBW.…”
Section: Dental Cariessupporting
confidence: 87%
See 1 more Smart Citation
“…Enamel hypoplasia is linked to celiac disease in some patients (Smith and Miller 1979;Wierink et al 2007) but as a non-specific stress indicator. It is also linked to environmental and societal stressors such as food shortage (Geber 2014), weaning (Ash et al 2016) and birth weight (Nelson et al 2013). Enamel hypoplasia can also be a hereditary condition (Robinson, Miller, and Worth1966).…”
Section: Celiac Disease Inferred From Pathological Morphologymentioning
confidence: 99%
“…[5]Also studies have revealed a reduction in the caries activity in children whose mothers used xylitol products [6,7] as xylitol significantly reduces the levels of mutans streptococci by disrupting the energy production processes leading to a futile energy consumption cycle and cell death. [6][7][8] Preterm infants and infants with very low birth weight experience a higher incidence of enamel (tooth) defects and enamel hypoplasia [9]. Periodontal disease has been linked to preterm labour [10].…”
Section: Introductionmentioning
confidence: 99%